Succinate dehydrogenase gene as a marker for studying Blastocystis genetic diversity - Adriana Higuera; Marina Muñoz; Myriam Consuelo López; Patricia Reyes; Plutarco Urbano; Oswaldo Villalobos; Juan David Ramírez (Heliyon, 2020)
Blastocystis has been reported as the most common eukaryotic microorganism residing in the intestines of both humans and animals, with a prevalence of up to 100% in some populations. Since this is a cryptic species, sequence polymorphism are the single strategy to analyses its genetic diversity, being traditionally used the analysis of ssu rRNA gene sequence to determine alleles and subtypes (STs) for this species. This multicopy gene has shown high diversity among different STs, making necessary to explore other genes to assess intraspecific diversity. This study evaluated the use of a novel genetic marker, succinate dehydrogenase (SDHA), for the typing and evaluation of the genetic diversity and genetic population structure of Blastocystis. In total, 375 human fecal samples were collected and subjected to PCR, subtyped using the ssu rRNA marker, and then the SDHA gene was amplified via PCR for 117 samples. We found some incongruences between tree topologies for both molecular markers. However, the clustering by ST previously established for Blastocystis was congruent in the concatenated sequence. SDHA showed lower reticulation (The origination of a lineage through the partial merging of two ancestor lineages) signals and better intra ST clustering ability. Clusters with geographical associations were observed intra ST. The genetic diversity was lower in the marker evaluated compared to that of the ssu rRNA gene (nucleotide diversity = 0.03344 and 0.16986, respectively) and the sequences analyzed showed population expansion with genetic differentiation principally among STs. The ssu rRNA gene was useful to explore interspecific diversity but together with the SDHA gene the resolution power to evaluate intra ST diversity was higher. These results showed the potential of the SDHA marker for studying the intra ST genetic diversity of Blastocystis related with geographical location and the inter ST diversity using the concatenated sequences.